5 minute stories - Lester, Helen; Munsinger, Lynn (Boston Houghton Mifflin Harcourt, 2015)
This value-packed collection features eight stories that will have kids laughing and learning important life lessons
"Includes downloadable audio!"--cover
ages 4 - 8 years
2
Keywords: Human behavior -- Juvenile fiction; Emotions -- Fiction; Hippopotamus -- Fiction; Elephants -- Fiction; Fairies -- Juvenile fiction; Rabbits -- Juvenile fiction; Listening -- Juvenile fiction; Swine -- Juvenile fiction; Selfishness -- Juvenile fiction; Witches -- Juvenile fiction; Names, Personal -- Juvenile fiction; Porcupines -- Juvenile fiction; Rhinoceroses -- Juvenile fiction; Princesses -- Juvenile fiction; Parrots -- Juvenile fiction; Sloths -- Juvenile fiction; Schools -- Juvenile fiction; Wild boar -- Juvenile fiction; Pigs -- Fiction; Behavior -- Fiction; Gnomes -- Fiction